PENGARUH BASIC SEDIMENT AND WATER TERHADAP LAJU KOROSI PIPA X52 DAN A53 PADA MEDIA OIL SLUDGE. - Naufan Arviansyah; Sumarji Sumarji; Digdo Listyadi Setyawan (ROTOR, 2017)
This research have a purpuse to know corrosion rate in pipe X52 and A53 at oil sludge media caused BS and W. Corrosion is a damage of metal that occurs because reaction between metal with environtment and produce unwanted of corrosion product. Pipe X52 and A53 is a type of low carbon steel that use for fluid transportation system in industry. Oil sludge is a sediment of crude oil from main gathering storage and containing variouses elements. Oil sludge have a one of element is Basic Sediment and Water that is can make corrosion happen to distribution pipes. Measuring Method used in this research is weight loss method. The result of corrosion rate in Oil Sludge media containing 30,17% BS and W for pipe A53 is 1,64 x 10-2 mmpy and the result for pipa X52 is 2,47 x 10-2 mmpy. The result of corrosion rate in Oil Sludge media containing 60,67% BS and W for pipe A53 is 2,12 x 10-2 mmpy and for pipe X52 the result is 3,13 x 10-2 mmpy. The result of this research showed pipe A53 have more resistance than pipe X52. The corrosion is classified as uniform corrosion. Keywords : A53, Weight Loss, Oil Sludge, X52.